2009
DOI: 10.1093/humrep/dep012
|View full text |Cite
|
Sign up to set email alerts
|

A novel embryonic stem cell line derived from the common marmoset monkey (Callithrix jacchus) exhibiting germ cell-like characteristics

Abstract: The cjes001 cells represent a new pluripotent ESC line with evidence for enhanced spontaneous differentiation potential into germ cells. This cjes001 line will be very valuable for comparative studies on primate ESC biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 42 publications
4
71
0
1
Order By: Relevance
“…Each marmoset ES cell line also showed a unique gene expression profile: clone No. 40 expressed NR6A1 (GCNF) but not BOLL (BOULE), whereas clone cjes001 exhibited the opposite expression in the previous report (Muller et al 2009). It remains to be elucidated whether there is any further correlation between marker gene expression and the differentiation potency of ES cells.…”
Section: Molecular Signature Of Marmoset Spermatogenesismentioning
confidence: 65%
See 1 more Smart Citation
“…Each marmoset ES cell line also showed a unique gene expression profile: clone No. 40 expressed NR6A1 (GCNF) but not BOLL (BOULE), whereas clone cjes001 exhibited the opposite expression in the previous report (Muller et al 2009). It remains to be elucidated whether there is any further correlation between marker gene expression and the differentiation potency of ES cells.…”
Section: Molecular Signature Of Marmoset Spermatogenesismentioning
confidence: 65%
“…To date, others and we have established several lines of marmoset ES cells (Sasaki et al 2005, Muller et al 2009) and induced pluripotent stem cells from fetal liver cells and neonatal skin fibroblasts (Tomioka et al 2010, Wu et al 2010. Both types of pluripotent stem cells were able to differentiate in vitro, suggesting the potential for in vitro germ cell production.…”
Section: Molecular Signature Of Marmoset Spermatogenesismentioning
confidence: 99%
“…c-CBL plays an important role in myeloid cells since mutations in this gene result in myeloid malignancies (Murati et al, 2012;Katzav and Schmitz, 2015;Lv et al, 2017). The role of c-CBL in human spermatogonia has not been investigated in detail so far since, to our knowledge, the fertility status and testicular histology of the patients carrying c-CBL mutations has not been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…c-CBL also plays an important clinical role. Myeloid malignancies originate from hematopoietic stem or progenitor cells of the myeloid lineage and mutations in the c-CBL gene have been found in many patients with this type of blood cell malignancies (Murati et al, 2012;Katzav and Schmitz, 2015;Lv et al, 2017). Using a combined microarray and immunohistochemistry approach, von Kopylow and colleagues (von Kopylow et al, 2010) further demonstrated that c-CBL is expressed in the human testis specifically by spermatogonia.…”
Section: Introductionmentioning
confidence: 99%
“…Marmosets were the first transgenic primates to demonstrate germline transmission 12 and their amenability to stem cell technologies is notable among primates. [13][14][15] They have also been suggested as particularly suitable models for gene therapy studies. 16,17 Part of the reason for this may be their limited MHC diversity, unique among primates.…”
mentioning
confidence: 99%